2009
DOI: 10.3174/ajnr.a1695
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Exercise on the Cerebral Vasculature of Healthy Aged Subjects as Visualized by MR Angiography

Abstract: BACKGROUND AND PURPOSE:Prior studies suggest that aerobic exercise may reduce both the brain atrophy and the decline in fractional anisotropy observed with advancing age. It is reasonable to hypothesize that exercise-induced changes to the vasculature may underlie these anatomic differences. The purpose of this blinded study was to compare high-activity and low-activity healthy elderly volunteers for differences in the cerebrovasculature as calculated from vessels extracted from noninvasive MR angiograms (MRAs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
80
0
6

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(88 citation statements)
references
References 35 publications
2
80
0
6
Order By: Relevance
“…With exercise, humans exhibit gray and white matter volume increases, 2 increases in microvascular density, and decreased cerebrovascular tortuosity. 42 Experimental animals on exercise regimes have shown increases in brain volume and cortical thickness; [43][44][45][46] neurogenesis in the hippocampus; 1,10,13,[47][48][49] and angiogenesis in the cortex, 34,50,51 hippocampus, 48,49 and cerebellum. 45,52,53 While rodent studies to date employed different forms of environmental enrichment in addition to an exercise wheel, it appears that the running component is the driving force at least for the neurogenesis and increased brain-derived neurotrophic factor (BDNF) peptide levels seen within the hippocampus.…”
Section: Introductionmentioning
confidence: 99%
“…With exercise, humans exhibit gray and white matter volume increases, 2 increases in microvascular density, and decreased cerebrovascular tortuosity. 42 Experimental animals on exercise regimes have shown increases in brain volume and cortical thickness; [43][44][45][46] neurogenesis in the hippocampus; 1,10,13,[47][48][49] and angiogenesis in the cortex, 34,50,51 hippocampus, 48,49 and cerebellum. 45,52,53 While rodent studies to date employed different forms of environmental enrichment in addition to an exercise wheel, it appears that the running component is the driving force at least for the neurogenesis and increased brain-derived neurotrophic factor (BDNF) peptide levels seen within the hippocampus.…”
Section: Introductionmentioning
confidence: 99%
“…A testedzés ezenkívül a felfokozott keringésen keresztül jelentősen javítja az agy vérellátását és serkenti új erek képződését is [44], amely szerepet játszhat az agy anyagcsere-folyamatainak a szabályozásá-ban is [45]. Ezeket a változásokat nyomon lehet kö-vetni nemcsak az állatmodelleken, hanem humán vizsgálatok során is [46]. A modern képalkotó diagnosztika lehetővé tette embereken annak a vizsgálatát is, hogy a rendszeres testedzés milyen mértékben csökkenti az életkorral együtt járó strukturális romlás mértékét [47].…”
Section: Vo 2max éS Az éLetkorral Járó Neurodegenerációunclassified
“…Even though studies suggested aging may be associated with smaller cerebral vessels, Bullitt et al (2010) reported that vessel diameter reductions may be compensated for by an increase in vessel number and that both larger and smaller vessels were impacted. In a sub-study comparing active versus inactive older adults, Bullitt et al (2009) reported significantly lower vessel tortuosity along with a higher number of www.intechopen.com smaller vessels. In a separate conference paper, although cerebral blood flow velocity did not change, Rahman et al (2008) reported less variance in the cerebral blood flow velocity in those with higher physical activity levels.…”
Section: Magnetic Resonance Angiography and Exercise Impactmentioning
confidence: 99%
“…Investigating how exercise impacts the brain is akin to the first studies investigating how exercise impacted the heart and its related vasculature several decades ago. A limitation in several structural imaging studies (e.g., Marks et al 2010;Bullitt et al 2009;Colcombe et al, 2006) was lack of cognitive function testing -it is unknown if the improved brain structures found in the more active subjects would have translated into better cognitive function. Adding cognitive testing with magnetic resonance imaging (MRI) may help detect subtle changes that the standard cognitive test batteries if used alone, cannot.…”
Section: Limitations and Suggestionsmentioning
confidence: 99%